Artificial Intelligence Innovation in Accounting: Opportunities and Challenges for Business Sustainability in Egypt - Ahmed Talal (Journal of Business Innovation and Accounting Research, 2024)
The integration of Artificial Intelligence (AI) into accounting practices represents a transformative paradigm shift, offering significant opportunities while simultaneously posing substantial challenges to business sustainability, particularly in the Egyptian context. This study examines the multifaceted dimensions of AI innovation in accounting, analysing how these technological advancements can enhance operational efficiency, decision-making processes, and sustainable business practices among Egyptian enterprises. Through a comprehensive mixed-methods approach combining quantitative survey data and qualitative analysis, this research investigates the current state of AI adoption in Egyptian accounting practices, identifies critical barriers to implementation, and explores strategic pathways for leveraging AI to achieve business sustainability objectives. The findings reveal that while AI technologies offer substantial benefits, including improved financial reporting accuracy, enhanced predictive analytics, and streamlined operational processes, Egyptian businesses face unique challenges related to limited financial resources, gaps in technical expertise, complex data integration, and regulatory uncertainties. The study contributes to the growing body of literature on AI adoption in emerging economies by providing empirically-grounded insights into the specific opportunities and challenges confronting Egyptian enterprises seeking to harness AI innovations for sustainable competitive advantage in the accounting domain.